2005
DOI: 10.1016/j.ejcts.2004.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Technical problems and complications of axillary artery cannulation

Abstract: Objective: Cardiopulmonary bypass via the axillary artery is frequently used especially in aortic dissections. With an increased use of this technique problems were recognized too. We describe the technical problems and complications associated with axillary artery cannulation. Methods: Sixty-five patients underwent cannulation of the axillary artery. The indication for operation was acute aortic dissection type A in 57%, chronic aortic dissection in 8%, aortic aneurysm in 18%, pseudoaneurysm in 3%, and others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
2
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(152 citation statements)
references
References 8 publications
(17 reference statements)
2
135
2
6
Order By: Relevance
“…Schachner et al experienced complications in 14% and needed to change the routes in 11% of cases. 93) Although direct cannulation is simple and quick, it may necessitate addition or switch of routes due to an insufficient flow rate or it can be associated with damage to the axillary artery or even dissection to the aorta. 93,94) Wong et al reported weakness or numbness of the arm without arm ischemia, 95) potentially due to injury on the brachial plexus.…”
Section: Perfusion Routementioning
confidence: 99%
“…Schachner et al experienced complications in 14% and needed to change the routes in 11% of cases. 93) Although direct cannulation is simple and quick, it may necessitate addition or switch of routes due to an insufficient flow rate or it can be associated with damage to the axillary artery or even dissection to the aorta. 93,94) Wong et al reported weakness or numbness of the arm without arm ischemia, 95) potentially due to injury on the brachial plexus.…”
Section: Perfusion Routementioning
confidence: 99%
“…Schachner et al [23] reported their experience attained in 65 surgeries using CPB with axillary arterial access. Twenty patients were submitted to arterial cannulation using polytetrafluoroethylene grafts (PTFE), while direct cannulation was performed in the other patients.…”
Section: Right Axillary/right Subclavian Arterymentioning
confidence: 99%
“…The best access route, the use of grafts or direct cannulation of the artery and the complications of these different methods are still discussed today [13,14,18,[22][23][24][25].…”
Section: Right Axillary/right Subclavian Arterymentioning
confidence: 99%
“…In addition, during axillary artery cannulation, problems such as cerebral ischemia and ischemia of the upper extremities can occur; thus, it may not be useful in all cases. [12][13][14] Furthermore, the use of cannulation of the ascending aorta to treat acute aortic dissection has also been reported. 4,5,15,16) Some institutions (such as ours) use the Seldinger technique for artery puncture and cannulation, 15,17) while others use direct cannulation for ordinary open heart surgery.…”
Section: Intraoperative Parameter(s) (Table 2)mentioning
confidence: 99%